2021
DOI: 10.3390/life11020095
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal Immune Reconstitution Inflammatory Syndrome: From Blood and Cerebrospinal Fluid Biomarkers to Treatment Approaches

Abstract: Immune reconstitution inflammatory syndrome (IRIS) presents as an exaggerated immune reaction that occurs during dysregulated immune restoration in immunocompromised patients in late-stage human immunodeficiency virus (HIV) infection who have commenced antiretroviral treatments (ART). Virtually any opportunistic pathogen can provoke this type of immune restoration disorder. In this review, we focus on recent developments in the identification of risk factors for Cryptococcal IRIS and on advancements in our und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 142 publications
0
16
0
Order By: Relevance
“…Transcriptome analysis of hosts' diseased tissues has been an integral part of the discovery of immune response biomarkers. University of Minnesota Division of Infectious Diseases (USA) leads intensive transcriptomic studies for discoveries of novel biomarkers of immune reconstitution inflammatory syndrome (IRIS) in the HIV-infected population [105,106]. IRIS presents as an exaggerated immune reaction (in a form of cytokine release syndrome) that occurs in immunocompromised patients who have commenced antiretroviral treatments (ART) [106].…”
Section: Assessment Of Host Response By Rna-seqmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome analysis of hosts' diseased tissues has been an integral part of the discovery of immune response biomarkers. University of Minnesota Division of Infectious Diseases (USA) leads intensive transcriptomic studies for discoveries of novel biomarkers of immune reconstitution inflammatory syndrome (IRIS) in the HIV-infected population [105,106]. IRIS presents as an exaggerated immune reaction (in a form of cytokine release syndrome) that occurs in immunocompromised patients who have commenced antiretroviral treatments (ART) [106].…”
Section: Assessment Of Host Response By Rna-seqmentioning
confidence: 99%
“…University of Minnesota Division of Infectious Diseases (USA) leads intensive transcriptomic studies for discoveries of novel biomarkers of immune reconstitution inflammatory syndrome (IRIS) in the HIV-infected population [105,106]. IRIS presents as an exaggerated immune reaction (in a form of cytokine release syndrome) that occurs in immunocompromised patients who have commenced antiretroviral treatments (ART) [106]. Several predictive and diagnostic biomarkers have already been identified in peripheral blood, utilizing Galaxy, JMP Genomics, or Partek Flow software (Figure 1).…”
Section: Assessment Of Host Response By Rna-seqmentioning
confidence: 99%
“… 3 It has been reported that approximately 25% of HCM patients develop CM-IRIS in the first 4 months of ART, with an average mortality of 20 ± 10%. 4 Thus, an effective treatment for IRIS would be helpful to decrease the likelihood of cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that this phenomenon occurs because of persistent intracranial in ammation mediated brain injury [9].Despite the ART, the residual low levels of viral replication from HIV latent reservoirs and the subsequent antiviral immune response may be the cause of sustained immune activation in the central nervous system (CNS) [10].Subsequently, the positive feedback loop of immunemediated tissue damage and repair processes can lead to persistent chronic CNS in ammation [9].On the one hand, chronic CNS in ammation caninduce neuronal insults, leading to cognitive dysfunction [11],and on another hand, continuous intracranial in ammation can lead to increased intracranial pressure and brain oedema, thereby increasing the risk of seizures and brain herniation [12].Therefore, safe and effective interventions are urgently needed for these patients to manage persistent intracranial in ammation to improve their clinical outcomes.Mechanismstudies suggest thatthepersistent intracranial in ammationare characterized by high levels of CSF T helper1 (Th1)associated proin ammatory cytokines suchasinterferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), granulocyte colony-stimulating factor (G-CSF) and interleukin(IL)-6 [13,14]. Thus, anti-in ammatory or immunomodulatory methods have become the primarytherapy options for persistent intracranial in ammation.Several case reports documented neurological improvement after the use of immunosuppressive drug corticosteroids, hydroxychloroquine thalidomide and adalimumab [15]. However, due to the lack of prospective clinical trial data and the small number of patients treated, it is not yet su cient to judge the e cacy and safety of the above immune modulators [16].…”
Section: Introductionmentioning
confidence: 99%